2006
DOI: 10.1080/00926230600835361
|View full text |Cite
|
Sign up to set email alerts
|

Treating Erectile Dysfunction through Electronic Consultation: A Pilot Study

Abstract: We investigated a group of men suffering from electric dysfunction (ED) who visited the website www.erectie.info and who had received consultation through the Internet (n = 219). We measured the treatment's effectiveness using the 5-item version of the International Index of Erectile Function (IIEF-5; Rosen et al., 1996; Rosen, Cappelleri, Smith, Lipsky, & Pena, 1999) and a global assessment question (GAQ). We investigated the motives and characteristics of the users of electronics consultation using a questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…For example, men randomized to an Internet-delivered cognitive behavior therapy for erectile dysfunction showed improved erectile performance at the 6-month follow-up compared to those in a control condition (Andersson et al, 2011). These results are supported by findings from another study, with the authors suggesting that this medium for delivering erectile dysfunction intervention may be most beneficial for men who appreciate the convenience of the Internet and who are embarrassed by attending in-person therapy (Leusink & Aarts, 2006). Although the use of online social networking websites is high among adults living in the United States (US) (Brenner & Smith, 2013), few technology-delivered sexual health interventions incorporate peer-to-peer features that may be an important source of support for clients.…”
supporting
confidence: 62%
“…For example, men randomized to an Internet-delivered cognitive behavior therapy for erectile dysfunction showed improved erectile performance at the 6-month follow-up compared to those in a control condition (Andersson et al, 2011). These results are supported by findings from another study, with the authors suggesting that this medium for delivering erectile dysfunction intervention may be most beneficial for men who appreciate the convenience of the Internet and who are embarrassed by attending in-person therapy (Leusink & Aarts, 2006). Although the use of online social networking websites is high among adults living in the United States (US) (Brenner & Smith, 2013), few technology-delivered sexual health interventions incorporate peer-to-peer features that may be an important source of support for clients.…”
supporting
confidence: 62%
“…As well as offering convenience and privacy, online therapies can simultaneously draw together a community of clients while maintaining their anonymity (Jones & McCabe, 2011;Leusink & Aarts, 2006;Tate & Zabinski, 2004). Research into the use of Internet-based interventions for sexual dysfunctions is quite limited, but preliminary evidence from studies investigating online CBT treatments for male sexual dysfunction (MSD) suggest that Internet-based treatment may be a suitable alternative to face-to-face sex therapy (Leusink & Aarts, 2006;McCabe, Price, Piterman, & Lording, 2008;van Diest, van Lankveld, Leusink, Slob, & Gijs, 2007;van Lankveld, Leusink, van Diest, Gijs, & Slob, 2009). Data from the study by Leusink and Aarts (2006) demonstrated that 81% of participants had improved erectile function scores at the completion of therapy.…”
Section: Incorporating Mindfulness and Chat Groups Into An Online Cogmentioning
confidence: 99%
“…Research into the use of Internet-based interventions for sexual dysfunctions is quite limited, but preliminary evidence from studies investigating online CBT treatments for male sexual dysfunction (MSD) suggest that Internet-based treatment may be a suitable alternative to face-to-face sex therapy (Leusink & Aarts, 2006;McCabe, Price, Piterman, & Lording, 2008;van Diest, van Lankveld, Leusink, Slob, & Gijs, 2007;van Lankveld, Leusink, van Diest, Gijs, & Slob, 2009). Data from the study by Leusink and Aarts (2006) demonstrated that 81% of participants had improved erectile function scores at the completion of therapy. McCabe and colleagues (2008) reported that 83% of males were able to obtain an erection at posttest following Internet-based treatment.…”
Section: Incorporating Mindfulness and Chat Groups Into An Online Cogmentioning
confidence: 99%
“…Internet-based treatment is likely to be particularly well-suited to men with ED, as this form of therapy removes the anxiety and embarrassment about discussing sexual problems in the company of a clinician. [10][11][12] Several researchers have recognized the benefits of the internet for addressing sexual health concerns. Hall 11 conducted a pilot study of an online task-based sex therapy program for treating various male and female sexual dysfunctions.…”
Section: Introductionmentioning
confidence: 99%